Securitizaç\~ao de ativos públicos para financiamento de projetos de infraestrutura: O caso Brasileiro e a experiência dos BRICS - Edison Benedito da Silva Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The study assesses the key challenges and opportunities for securitization of public assets as a way to foster investment in the infrastructure sector in Brazil and to improve the domestic capital market. The securitization of public assets offers advantages for public financing of infrastructure projects and the strengthening of the capital market in Brazil, as evidenced by recent examples of the BRICS (Brazil, Russia, India, China and South Africa). However, it demands not only improving the institutional and financial framework that provides support for infrastructure projects, but also public accounting standards that should be be aligned with the best market practices. In this sense, in addition to boost infrastructure projects, public-private partnerships and foreign investment may also play an important role in improving the management of public assets in Brazil.
Keywords: G38; L32; O16; O18; 330; securitization; public assets; infrastructure; public-private partnerships